Horizon Learning Model (Active and Creative Ways to Realize Hopes Through Meaningful Learning) on the Topic - Waste Management in the School Environment - Hasrinah Hasrinah; Muhiddin Palennari (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study discusses the development of the CAKRAWALA Learning Model (Active and Creative Ways to Realize Aspirations through Meaningful Learning) on the topic of Waste Management in the School Environment as a strategic effort to enhance students' character values, collaboration, environmental awareness, creativity, and social responsibility. The implementation of the CAKRAWALA model in Biology education acts as a metaphor for expanding students' understanding from a narrow conceptual scope toward a holistic ecological perspective. The research method applied in this study is a literature review. The results show that the CAKRAWALA model is effectively implemented in contextual project-based learning, especially in waste management topics within school environments. The model integrates character values, collaboration, and environmental awareness in a meaningful and enjoyable way through the following steps: Create a Conducive Atmosphere (Preparation and Motivation), Experience the Material Deeply (Concept Exploration), Develop Understanding (Discussion and Analysis), Summarize and Conclude (Reflection and Generalization), Apply Knowledge (Implementation and Practice), Realize Creative Projects (Innovation and Collaboration), Conduct Holistic Assessment (Comprehensive Evaluation), Continue Independent Learning (Ongoing Development), and Appreciation and Evaluation (Feedback and Celebration).